Declarative and Payment Obligations Regarding the Taxation of the Income Made by Independent Persons from Intellectual Property Rights - Lucian CERNUȘCA (CECCAR Business Review, 2023)

(untitled)
The article hereby brings into focus a series of theoretical and practical aspects regarding the taxation of incomes made of intellectual property rights in case the beneficiaries are independent taxable persons. They have the possibility to decide on setting the income according to the rules of the flat rate system or according to the actual taxation one. Alongside the income tax, taxpayers still have obligations with regard to social contributions under certain conditions provided by the Fiscal code. During the year 2023, they will make the assessment in view of setting up possible payment obligations of the social insurance contribution and the social health insurance contribution. Finalizing the income made by them in the year 2023, which is at the basis of setting the final obligations as regards social contributions, shall be made in the following year (2024), by filling in chapter I in the single return.